2019
DOI: 10.1182/bloodadvances.2019000093
|View full text |Cite
|
Sign up to set email alerts
|

BRAF-V600E–mutated Rosai-Dorfman-Destombes disease and Langerhans cell histiocytosis with response to BRAF inhibitor

Abstract: Key Points Demonstration of BRAF-V600E in Rosai-Dorfman-Destombes disease requires sensitive molecular assays and molecular-based tissue immunostain. BRAF-V600E blood testing is important for disease-monitoring BRAF-mutated histiocytosis and can guide inhibitor treatment plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
(41 reference statements)
0
26
0
Order By: Relevance
“…Scattered RDD-like cells with emperipolesis and variable light S100 staining has been previously noted in cutaneous JXG-family lesions [33, 54]. Furthermore BRAF V600E mutations have also been identified in rare cases of RDD [25, 44], including a variant BRAF mutation with CNS disease [52], which further emphasizes that morphology combined with molecular are useful for accurate diagnosis.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Scattered RDD-like cells with emperipolesis and variable light S100 staining has been previously noted in cutaneous JXG-family lesions [33, 54]. Furthermore BRAF V600E mutations have also been identified in rare cases of RDD [25, 44], including a variant BRAF mutation with CNS disease [52], which further emphasizes that morphology combined with molecular are useful for accurate diagnosis.…”
Section: Discussionmentioning
confidence: 83%
“…In the post-BRAF era, we now turn our attention to the molecular classification of histiocytic neoplasms as an area of ongoing, active investigation, which now includes extracutaneous JXG with BRAF V600E and MAPK pathway mutations, in addition to LCH and ECD with BRAF V600E mutations, and even rare reports of RDD with BRAF V600E [25, 44]. Thus, the question of whether the L-group histiocytic group should include only LCH/ECD or whether a more inclusive category of “MAPK-pathway activated histiocytoses” should now exist for all groups will need further discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-BRAF V600E immunohistochemistry was strongly positive in both RDD and LCH, and BRAF p.V600E mutation was detected on peripheral blood mononuclear cells. 20 Richardson et al 19 demonstrated a single somatic pathogenic mutation in exon 12 of the BRAF gene (p.486-491del) Types of lymphoma include Hodgkin's lymphoma-classic (8) 25 26 35 and nodular lymphocyte predominant (8) 35 36 and non-Hodgkin's lymphoma-follicular (2), 25 T cell (3), [29][30][31] small lymphocytic lymphoma (2), 35 37 Mantle cell (1), 38 marginal zone lymphoma (3), 35 39 40 diffuse large B cell lymphoma (4), 27 28 41 42 mycosis fungoides (1) 32 and other (large cell immunoblastic and small non-cleaved, 2). 33 34 Types of leukaemia include acute myeloid leukaemia (1) 43 and acute lymphoblastic leukaemia (2).…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…By and large, these somatic alterations affect the RAS-MAPK pathway, with the frequency of specific genetic defects varying between disorders. For example, although the BRAF V600E mutation is identified in approximately one-half of all cases of LCH and Erdheim-Chester disease, 7,17 it is rare in Rosai-Dorfman disease (RDD) 18,19 and even rarer in JXG. 20,21 An increasing number of studies in the literature describe the somatic mutations other than BRAF V600E found in JXG tumors.…”
Section: Genomic Testingmentioning
confidence: 99%